Study of serum cobalamin level in vegetarian v/s nonvegetarian geriatric individuals - Mishra, V. N.; Mishra, Nalini; Khandelwal, Rohit (International Journal of Research in Medical Sciences, 2017)
Background: Vegetarianism is found in all geographic areas, they may have lower B-12 levels than nonvegetarian; problem could be graver in elderly. This study intended to recognise geriatric individuals with B-12 deficiency so as to save them from anaemia, dementia & neuropsychiatric disturbances by timely recommendations for supplementation. Methods: Current study was conducted on 200 healthy attendants divided in to two groups- A comprised of 100 vegetarian and B of 100 nonvegetarian geriatric individuals (> 60yrs.), they had no previous chronic disease and an attempt was made to exclude diabetes mellitus, hypertension, chronic gastritis, hypoplastic & aplastic anaemia. Those with history of alcohol intake, PPI therapy & regular vitamin supplementation were excluded. Complete clinical examination and routine blood tests were done. Serum cobalamin level was determined by ACCU-BIND ELISA Microwells method. Results: Total of 58 vegetarians were found to be B-12 deficient compared to 42 normal (>350pg/ml) this was statistically significant. Out of 100 nonvegetarian 48 were deficient while 52 had normal levels this too was statistically significant. On comparing the vegetarians and non vegetarian groups significant result was obtained (p <0.01). When different age groups were statistically compared insignificant result was obtained, same was true for gender distribution. Statistically significant result was obtained on comparing vegetarian Vs nonvegetarian group. Conclusions: Irrespective of the dietary habit B-12 deficiency is prevalent in elderly, as 58% of vegetarian & 48% of nonvegetarian were found B-12 deficient, detailed dietary analysis revealed that majority of them consumed nonvegetarian food only occasionally. No significant effect of increasing age & gender was found on B-12 levels in either group. Every elderly vegetarian or non vegetarian irrespective of gender should get their B-12 levels checked & if found low should receive B-12 supplement.